Determining The Prevalence Of Family Planning (FP) Utilisation And Its Associated Factors Among Adults In Malaysia: An Online Survey. - Nadeeya'ayn Umaisara Mohamad Nor; Zairina A. Rahman; Akmal Hisham Bin Shamshul Bahri; Amirah Azzeri; Mohamed Fakhri Abu Baharin; Nizam Baharom; Mohd Dzulkhairi Mohd Rani; Aza Sherin Mohamad Yusuff; Hafiz Jaafar; Tengku Amatullah Madeehah Tengku Mohd; Ahmad Taufeeq Bin Basri; Nadia Binti Yazid (Zes Rokman Resources, 2024)
Background: Family Planning (FP) is one of the pillars of Safe Motherhood Program in reducing maternal mortality and morbidity. Despite positive evidence on the benefit of family planning, its utilisation among Malaysian population is still lower than expected. This study aimed to determine the prevalence of family planning utilisation and its associated factors among adults in Malaysia. Methods: An online survey was conducted involving 402 respondents of Malaysian adults. Convenience sampling was used in recruiting the respondents. Pretested questionnaire was distributed using online google form through various social media platform. Family planning utilisation was defined as the usage of any contraceptive methods (modern or traditional) within the past one year. The independent variables studied were sociodemographic characteristics, knowledge and attitude towards family planning, presence of spousal communication for family planning and accessibility to the service. Results: Prevalence of FP utilisation was 49.0% with higher percentages noted among female, Malay, age between 24-35 years, married, completed tertiary education, middle income group (M40) and having one to five children. Mean (SD) scores of knowledge (9.01 (2.271) and attitude (42.20 (4.948) towards FP were higher among respondents who utilised FP. The accessibility rate for FP services was 69.9%. Multiple logistic regression analysis showed that predictors for FP utilisation were, high scores of knowledge (P=0.001) and attitude (P=0.026) towards FP, age group of 25-34 (P=0.001) together with 35-50 years old (P=0.001) and having 1 to 5 children in the family (P=0.011). Conclusion: Family planning utilisation remains low despite easily accessible services. Increasing knowledge, instils positive attitude and targeting towards suitable population are among the crucial elements to be focused in any intervention plans by the relevant authorities